Note on 'Competition in Two-sided Markets' - Yuyu Zeng; Harold Houba; Gerard van der Laan (Tinbergen Institute, 2015)
We extend the models in ("Competition in two-sided markets" of Armstrong (2006, Rand Journal of Economics) by adding within-group externalities. In the monopoly and duopoly cases, positive within-group externalities reduce the price of the own group. Negative externalities have an opposite price effect. In the case of a competitive bottleneck, we show by examples that within a certain range of parameter values, a novel phenomenon arises that the platform attracts more agents from one of the groups compared with the social optimum.
Keywords: D4; L4; 330; Competition economics; two-sided market